Pyrene binding to persistent micelles formed from a dendro-calixarene - Yihwa, Chang; Kellermann, Michael; Becherer, Miriam; Hirsch, Andreas; Bohne, Cornelia (Photochemical & Photobiological Sciences, 2007)
The formation of micelles of an amphiphilic dendro-calixarene (1) was studied using pyrene as a guest molecule. Steady-state fluorescence experiments were performed, which showed that pyrene is readily solubilized in the micelles and senses an environment with a moderate polarity. Time-resolved fluorescence measurements showed that pyrene in the micelles have two lifetimes, suggesting some compartmentalization of the guest within the micelles. Pyrene bound to the micelles is completely protected from the interaction with anionic species in the aqueous phase, due to the repulsion between the anions and the negatively charged micelles. Compared to conventional micelles, such as those formed with sodium dodecyl sulfate, micelles of 1 form at much lower concentrations of monomer. © The Royal Society of Chemistry and Owner Societies.